Effect of Otaria’s Postpartum Gymnastic Model and Caregiver Support on Decreasing of Uterine Fundus Height in Postpartum Mothers - Emy Rianti (Disease and Health Research: New Insights Vol. 8, 2024)
The cause of maternal death in Indonesia is still dominated by bleeding, hypertension followed by infection, prolonged labor, and abortion. One of the causes of the bleeding is uterine atony. Postpartum gymnastics is one of the efforts to restore the postpartum mother’s womb. Therefore, developing postpartum gymnastics for an effective gymnastic model is still needed. This study aimed to assess the effectiveness of the Otaria postpartum gymnastic model and caregiver assistance in reducing maternal uterine fundal height, using a matching pretest-posttest with the control group involving 160 postpartum mothers. The intervention group was treated with Otaria’s postpartum gymnastic model from the 1st to the 10th day. The control group was treated with early mobilization. The final results based on the General Linear Model-Repeated Measures (GLM-RM) for the difference (\(Δ\)) between uterine height in the intervention group and the control group showed that a very significant difference occurred on the 6th day to the 7th day postpartum with a difference of 1.65 cm (p<0.05). Exercises targeting specific muscles can enhance blood flow, increasing the transport of oxygen and other nutrients to the muscles, ultimately maximizing strength. In conclusion, implementing Otaria’s postpartum gymnastic model alongside caregiver assistance may facilitate the return of the uterine height to its normal state by the seventh day postpartum.